Pelatihan Pengembangan Administrasi Keuangan dan Pemasaran Bagi Pengusaha Mikro Perempuan di Kabupaten Kulon Progo - Nur Aini Yuniyarti; Achmad Choiruman; Nurisqi Amalia (Jurnal Pengabdian dan Pengembangan Masyarakat, 2018)
In order to overcome the existing poverty problem in Kulon Progo Regency, one of the ways taken by the Government is by empowering the women community through the formation of women group that joined in the group of Income Generating Enterprises for Family Welfare. The problem faced by most members of this group is the inadequate capability in the field of financial administration records and product marketing. The purpose of this service is to increase the capacity of these micro women entrepreneurs through a training in the field. The method used in this activity is to involve the active participants in thinking, discussing, and directly practicing by: 1) the workshop and training of development of financial administration, 2) Participant doing marketing practice by using social media (e-mail, Lazada online shopping site) with the media computer and mobile by each participant. The training was conducted in two stages. The first stage is training and development workshop financial administration. The second stage is the development of online marketing training with computers. The result that can be achieved from this activity is that micro women entrepreneurs increase their ability to manage the financial administration of business and private household; The formation of whatsApp group/group consisting of participants for the participant's marketing information network; and online marketing capabilities for the participants are growing well.